Oral Aspects A Performative Approach to 1QM - Haigh, Rebekah (2019)
As the product of a textual community imbedded in an oral culture, the War Scroll can be rewardingly approached as a composition intended for a community of hearers. Indeed, this article demonstrates that 1QM retained an orally fluid textuality and preserves a variety of textual indicators of performativity: hints of oral engagement, accumulation of imitable practices, and reliance on rhetorical techniques suited to the ear. In examining the performative potentials in the War Scroll's prescriptive (cols. 1-9), prayer (cols. 10-14), and dramatic (cols. 15-19) material, I argue that 1QM can be understood as a spoken text, one which lends itself to performance and embodiment.
Keywords: Dead Sea Scrolls; Qumran; War Scroll; Orality; Performance; textuality